Full‐term pregnancy with vaginal birth following dystocia and caesarean section in two cheetahs (Acinonyx jubatus). Issue 2 (21st May 2018) - Alves, Sara E; Joyner, Priscilla H; Aitken‐Palmer, Copper; Crosier, Adrienne E; Ware, Lisa
Abstract : The cheetah ( Acinonyx jubatus ) population in North American zoos remains unsustainable despite extensive management within the Species Survival Plan. Successful copulation, pregnancy and birth are essential to achieving population sustainability for this species. This case report discusses the clinical presentation and treatment of one five‐year‐old nulliparous and one six‐year‐old primiparous cheetah that presented with dystocia followed by caesarean section. It details postcaesarean complications due to abdominal herniation and uterine infection. Both females were rebred after recovery, giving birth vaginally without complications. These cases demonstrate the possibility of successful copulation, pregnancy and vaginal birth postdystocia and caesarean with proper management. Understanding reproductive complications and successful veterinary care during such obstacles is critical to providing appropriate welfare and care for animals under professional zoological care.